1986
DOI: 10.1111/j.1365-2052.1986.tb03191.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for BoLA‐linked resistance and susceptibility to subclinical progression of bovine leukaemia virus infection

Abstract: The role of the bovine major histocompatibility complex in bovine leukaemia virus (BLV) infection and disease progression was investigated in a herd of Shorthorn cattle (n = 117). The frequency of cows that were seropositive to BLV-glycoprotein antigen was 51%. Twenty-three per cent of the seropositive cows were lymphocytotic. At the herd level, relative resistance to BLV-dependent B-cell proliferation and lymphocytosis among seropositive cows was associated with bovine lymphocyte antigen (BoLA)-DA7, whereas s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
3

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 24 publications
2
50
0
3
Order By: Relevance
“…The present work confirms the existence of correlations between susceptibility to disease and a specific MHC haplotype reported in animal and man [1,5,10].…”
Section: Discussionsupporting
confidence: 91%
“…The present work confirms the existence of correlations between susceptibility to disease and a specific MHC haplotype reported in animal and man [1,5,10].…”
Section: Discussionsupporting
confidence: 91%
“…Recently, several reports showing the resistance to BLV infection is innately established by MHC have been accumulated [31,32,39,57,68]. Xu et al demonstrated that there was significant difference between PL and healthy group in the amino acids sequence in the DRB3 region of bovine leukocyte antigen (BoLA) class II [68].…”
Section: Blv-resistant Animalmentioning
confidence: 99%
“…First evidences revealed an association between resistance or susceptibility to PL and BoLA A class I alleles (LEWIN; BERNOCO, 1986); however, these associations were relatively weak at population levels and different BoLA A alleles had significant effects in different breeds (LEWIN et al, 1988;STEAR et al, 1988). Subsequent studies showed that resistance and susceptibility to PL map more closely to MHC class II BoLA DRB3.2 gene than to BoLA A locus (ESTEBAN et al, 2009).…”
Section: Introductionmentioning
confidence: 99%